Kingdom of Lesotho : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Lesotho. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that high levels of unemployment, poverty, and inequality persist in Lesotho despite its faster growth compared with regional peers over the last decade. GDP growth is expected to be about 3 percent in FY2017/18, below the average of 4.1 percent for the past decade, and driven by mining and agriculture. Over the next three years, GDP growth is expected to be led by mining and construction related to the Lesotho Highlands Water Project Phase II. A steep decline in Southern African Customs Union transfers, a major source of government revenue, will result in a fiscal deficit that is likely to exceed 6 percent of GDP for the second year.